Laju perambatan retak plat aluminium 2024 T3 dengan beban fatigue uniaksial pada rasio beban dan jarak diameter lubang berbeda - Luwar Sanyoto, Budi; Berata, Wajan (Jurnal Energi Dan Manufaktur, 2012)
Producing of component by machining process can yield component defective. That defective in crack form, although it probably is very litlle. If that defective is applied by a syclic load, the defective exist will propagate with a propagation rate until a limit where that structure is not able to restrain load applied to it. In this research, the specimen to be used was plat Al 2024 T3 with open hole, constant diameter and different distance between hole. Testing to be done by giving fatique load with ratio 0,3, according to ASTM standard E-647-93 (1994). The data to be collected were crack length and the number of load cyclic. Further, it is calculated crack propagation rate (da/dN) toward strength intensity factor (?K). The result of investigation shows that crack propagation rate curve of strength intensity factor function in the Paris area has Paris constant m = 1,163 until 4,2, and value of C = 1,69E-12 until 9, 34E-09
Keywords: Crack propagation rate, stress intensity factor, Paris constant.